The Influence of Guided Inquiry Learning Model using Thinking Empowering by Questioning Model on Learning Outcomes Cognitiv Students - Sukini, Sukini; Syafii, Wan; Yustina, Yustina (Journal of Educational Sciences, 2020)
This study aims to determine the effect of the Guided Inquiry (GI) learning model with Thingking Empowering By Questioning (TEQ) on student cognitive learning outcomes. This study was a quasi-experimental study with a pretest posttest control group design. The population of this research was the students of class XI MIPA SMAN 3Dumai in the academic year 2018/2019. Sampling method was done using random sampling techniques to getexperiment and control class. The parameters measured were cognitive learning outcomes and the instrument used was an objective test. The data analysis technique for testing hypotheses was independent t-test. Data analysis showed sig ˂ 0.05 then H0 was rejected, this shows that student learning outcomes with the Guided Inqury model with Thingking Empowering By Questioning were significantly different from student learning outcomes with conventional models. Student learning outcomes using the Guided Inqury learning model with Thingking Empowering By Questioning are better than student learning outcomes using conventional learning. The average value of student learning outcomes in the experimental class was 81.82 while the control class was61.29. The average N-gain of the experimental group was0.70 with a high category and the control group was 0.38with a moderate category.